Sistem Pendataan Laboratorium - Esther Joan Ruthmika Sianturi; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
SMK Pharmacy Ikasari Pekanbaru is medium-level health education institution that has laboratory supply section. The Laboratory Supply Section is tasked with providing practical needs for students. The disposable substance is the material which the student uses which runs out in one use. Managing disposable substance inventory data is still simple by using a printed list, then listing the remaining items. This creates difficulties because sometimes there are errors in recording the quantity of disposable substances. The Laboratory Supply Section requires systems that aim to monitor inventory levels and how many levels of inventory must be maintained, when supplies must be added, and how many orders must be made to meet the practicum needs of students in the laboratory. The solution to this problem is a web-based laboratory inventory system that can be used as a medium that can help manage disposable substance data in Pharmacy Laboratory. This system is equipped with notification feature via email notification. Functionality testing is also carried out using the black box testing method. From the results of black box testing, there were no errors found in any testing process. Keywords : Laboratory Inventory System, Web